Annotated bird sighting list for Spring 1986 compiled by Tom Staudt - Staudt, Thomas J.et al (1986)
An annotated list of birds sighted by Tom Staudt and four others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1986. Epson - sheet feed